In Ganoderma lucidum, Glsnf1 regulates cellulose degradation by inhibiting GlCreA during the utilization of cellulose. (28th October 2019) - Hu, Yanru; Xu, Wenzhao; Hu, Shishan; Lian, Lingdan; Zhu, Jing; Shi, Liang; Ren, Ang; Zhao, MingWen
Summary: Cellulose is a by‐product of agricultural production and an abundant waste. As a carbon source, cellulose can be degraded and utilized by fungi. Carbon sources, which act as nutrients, not only provide energy but also serve as regulators of gene expression, metabolism and growth, through various signalling networks that enable cells to sense and adapt to varying environmental conditions. Nutrient‐sensing pathways prioritize the use of preferred carbon sources and regulate the production of cellulose‐degrading enzymes when necessary. Understanding the regulation of the fungal cellulolytic response will become increasingly important because we strive to increase the efficiency of the utilization of these renewable energy sources. Here, we show that Glsnf1, a sucrose‐nonfermenting serine–threonine‐protein kinase 1 (Snf1)/AMP‐activated protein kinase homologue in medicinal macro basidiomycete Ganoderma lucidum, actively responds to carbon alterations and positively regulates cellulase activity and cellulase‐related gene transcription. The carbon catabolite repressor CreA, a zinc binuclear cluster transcription factor that mediates the sensing of nutrients and suppression of the transcription of a number of genes necessary for the consumption of a less preferred carbon source, participates in the Glsnf1‐mediated regulation of cellulases. Glsnf1 not only negatively regulates the transcription level of the CreA gene but also hinders its localization in the nucleus. Overall, our findings reveal a key nutrient‐sensing mechanism that is critical for the modulation of carbon source adaptation in G . lucidum .